Tropospheric and total ozone columns over Paris (France) measured using medium-resolution ground-based solar-absorption Fourier-transform infrared spectroscopy - C. Viatte (Atmospheric Measurement Techniques, 2011)
Ground-based Fourier-transform infrared (FTIR) solar absorption spectroscopy is a powerful remote sensing technique providing information on the vertical distribution of various atmospheric constituents. This work presents the first evaluation of a mid-resolution ground-based FTIR to measure tropospheric ozone, independently of stratospheric ozone. This is demonstrated using a new atmospheric observatory (named OASIS for "Observations of the Atmosphere by Solar absorption Infrared Spectroscopy"), installed in Créteil (France). The capacity of the technique to separate stratospheric and tropospheric ozone is demonstrated. Daily mean tropospheric ozone columns derived from the Infrared Atmospheric Sounding Interferometer (IASI) and from OASIS measurements are compared for summer 2009 and a good agreement of −5.6 (±16.1) % is observed. Also, a qualitative comparison between in-situ surface ozone measurements and OASIS data reveals OASIS's capacity to monitor seasonal tropospheric ozone variations, as well as ozone pollution episodes in summer 2009 around Paris. Two extreme pollution events are identified (on the 1 July and 6 August 2009) for which ozone partial columns from OASIS and predictions from a regional air-quality model (CHIMERE) are compared following strict criteria of temporal and spatial coincidence. An average bias of 0.2%, a mean square error deviation of 7.6%, and a correlation coefficient of 0.91 is found between CHIMERE and OASIS, demonstrating the potential of a mid-resolution FTIR instrument in ground-based solar absorption geometry for tropospheric ozone monitoring.